Expressing concern and writing it down: an experimental study investigating transfer of information at nursing handover. (18th July 2014) - Lee, Henrietta; Cumin, David; Devcich, Daniel A.; Boyd, Matt
Abstract Aims To examine the effects of two factors on the transmission of clinical information at nursing handover. These factors were: (i) an affective statement expressing concern about the information; and (ii) verbal reference to a written summary of the information. Background Quality of communication at patient handover is inconsistent, compromising patient safety. Little is known about the nuances of communication that lead to effective handovers. Furthermore, effective information transmission during handovers is seldom evaluated using experimental research designs. Design A randomized, single‐blind, controlled experiment. Methods Postanaesthesia care unit or surgical ward nurses and final‐year nursing students were randomly assigned to watch one of four versions of a video‐recorded handover. In each version, one piece of information was presented as either a simple statement (control), with an affective qualifier, with a written summary of the information, or with both an affective qualifier and a written summary. Primary outcome was assessed by questionnaire following a task directing attention away from the handover. Data were collected July–October, 2013 and analysed using 2 × 2 anova. Results A total of 157 nurses participated. Successful transmission of the clinical information did not significantly differ across the experimental conditions. Subgroup analysis revealed significantly higher transmission success among more experienced nurses when the affective statement was present compared to when it was absent (Kruskal–Wallis P = 0·002). Conclusions Expressing concern about information or directing attention to written notes may not improve information transfer at handover. However, affective qualifiers may have differential receiver‐specific influences on information retention.